The impact of airport road wayfinding design on senior driver behaviour - Anuar, Nur Khairiel (Cranfield University, 2016)
Airport road access wayfinding refers to a process in which a driver makes a decision to navigate using information support systems in order to arrive to airport successfully. The purpose of this research is to evaluate senior drivers’ behaviour of alternative airport road access designs. In order to evaluate the impact of wayfinding, the combination of simulated driving and completion of a questionnaire were performed. Quantitative data was acquired to give significant results justifying the research outcomes and allow non-biased interpretation of the research results. It represents the process within the development of the methodology and the concept of airport road access design and driving behaviour. Wayfinding complexity varied due to differing levels of road-side furniture. The simulated driving parameters measured were driving mistakes and performances of senior drivers. Three types of driving scenarios were designed consisting of 3.8 miles of airport road access. 40 senior drivers volunteered to undertake these tasks. The questionnaire was used as a supporting study to increase the reliability and validity of the research. Respondents who volunteered for the simulated driving test were encouraged to participate in the questionnaire sessions. The questionnaire was answered after each simulation test was completed. The Mean, Standard Deviation (SD) and Two-Way ANOVA test were used to analyse the results and discussed with reference to the use of the driving simulation. The results confirmed that age group has no significant effect of airport road access complexity design on driving behaviour. Although many studies have been conducted on wayfinding in general, a detailed evaluation on airport road access wayfinding network and driving behaviour in respect of senior drivers were still unexplored domains.
Keywords: Wayfinding; Airport; Senior driver; Driving behaviour; Simulation